2017
DOI: 10.1186/s13148-017-0365-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms during ageing and neurogenesis as novel therapeutic avenues in human brain disorders

Abstract: Ageing is the main risk factor for human neurological disorders. Among the diverse molecular pathways that govern ageing, epigenetics can guide age-associated decline in part by regulating gene expression and also through the modulation of genomic instability and high-order chromatin architecture. Epigenetic mechanisms are involved in the regulation of neural differentiation as well as in functional processes related to memory consolidation, learning or cognition during healthy lifespan. On the other side of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 244 publications
(250 reference statements)
1
81
0
Order By: Relevance
“…The influence of DNA methylation in gene transcription can be stable and heritable across cell generations, and also reversible according to external condition changes [23]. The dynamics of DNA methylation plays a vital role in the pathogenesis of SCZ, especially in neuronal diversity, plasticity and neurogenesis [24, 25]. Besides environmental and developmental effects, DNA methylation can also be influenced by sequence variants (e.g., genotype variation or specific allele on a locus), which represents a methylation QTL (meQTL).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of DNA methylation in gene transcription can be stable and heritable across cell generations, and also reversible according to external condition changes [23]. The dynamics of DNA methylation plays a vital role in the pathogenesis of SCZ, especially in neuronal diversity, plasticity and neurogenesis [24, 25]. Besides environmental and developmental effects, DNA methylation can also be influenced by sequence variants (e.g., genotype variation or specific allele on a locus), which represents a methylation QTL (meQTL).…”
Section: Introductionmentioning
confidence: 99%
“…Many behavioral traits, including cognitive functions, may be transgenerationally affected by experiences and environmental factors in mammals, most likely through epigenetic mechanisms [92]. Memory is an essential cognitive function which declines during aging and is impaired in most neurodegenerative diseases such as Alzheimer's disease; it is subjected to various epigenetic regulations, providing novel therapeutic avenues to combat cognitive disorders [12,93]. Therefore, studying TEI of memory is of immense importance to our understanding of mental health and diseases.…”
Section: Memorymentioning
confidence: 99%
“…In this context, it is plausible that the aging‐associated changes in gene expression may be because of alteration in DNA methylation (DNAm) in the brain. In fact, several studies have demonstrated age‐associated DNAm, such as hypermethylation or hypomethylation, in the brain . With regard to BDNF, Keleshian and associates reported that the methylation rate at promoter I of the BDNF gene in the frontal cortex was positively correlated with aging.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have demonstrated age-associated DNAm, such as hypermethylation or hypomethylation, in the brain. [10][11][12][13][14] With regard to BDNF, Keleshian and associates 15 reported that the methylation rate at promoter I of the BDNF gene in the frontal cortex was positively correlated with aging. McKinney and colleagues 16 also demonstrated that methylation levels at the promoters of the BDNF gene in the orbital frontal cortex in an elderly cohort were higher than those in a younger cohort.…”
Section: Introductionmentioning
confidence: 99%